Multiple futures for society, research, and innovation in the European Union: Jumping ahead to 2038 - Stephanie Daimer; Attila Havas; Kerstin Cuhls; Merve Yorulmaz; Petar Vrgovic (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2021)
We contribute to the Responsible Research and Innovation (RRI) literature in two ways: (i) we consider how societal aspects are taken into account in research and innovation activities in four fundamentally different futures, as opposed to analysing current practices; and (ii) put the emphasis on the framework conditions, as opposed to focussing on RRI principles and instruments. In the Kingdom of RRI citizens participate directly in decision-making processes; Fortress Europe depicts a libertarian system; Failed Democracy is a populist regime; while Benevolent Green Eurocrats describes a technocratically coordinated strong state. The RRI concept is ignored, manipulated, or rather selectively applied in the latter three scenarios. The scenarios offer novel insights into the nature and repercussions of possible policy problems. We discuss issues related to efficacy and efficiency of policy-making; legitimacy of research and innovation activities; societal involvement; equity; and freedom of research in each scenario. We also posit that there is room for safeguarding meaningful interactions between the societal and professional actors in an innovation system even in the harshest framework conditions.
Keywords: F50; F52; H10; H11; O20; O25; O30; O31; O32; O33; O38; P11; P18; Q54; Q55; Q56; 330; Responsible Research and Innovation (RRI); Interactions between societal and professional actors (ISPA); Ideological stances on ISPA; Futures of ISPA